Анализ перспектив и методов использования газогенераторного газа с целью разработки энергоэффективных решений по экономии энергоресурсов - Гридин, С. В.; Вертела, С. А. (НТУ "ХПИ", 2013)
В статье рассматривается общий процесс получения синтез газа методом подземной газификации и возможные перспективы его дальнейшего использования.

The paper considers the overall process of production of synthetic gas by the underground gasification method and possible perspectives of its further use
Analysis of perspectives and methods of use of gas produced by gas plant in order to develop energy effective solutions for energy saving
Keywords: синтез газа; подземная газификация; дальнейшие перспективы; synthetic gas; underground gasification method; possible perspectives